2019
DOI: 10.1101/733527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic turnover of centromeres drives karyotype evolution in Drosophila

Abstract: Centromeres are the basic unit for chromosome inheritance, but their evolutionary dynamics is poorly understood. We generate high--quality reference genomes for multiple Drosophila obscura group species to reconstruct karyotype evolution. All chromosomes in this lineage were ancestrally telocentric and the creation of metacentric chromosomes in some species was driven by de novo seeding of new centromeres at ancestrally gene--rich regions, independently of chromosomal rearrangements. The emergence of centromer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 131 publications
(133 reference statements)
1
29
0
Order By: Relevance
“…BUSCO results suggest our final scaffolded genome assembly is of high quality and 181 95.7% of BUSCOs were found complete (Table 1). We found the BUSCO statistics to be slightly 182 lower than our other high-quality obscura group assemblies which average 98.7% complete 183 (Bracewell et al 2019). To investigate this reduction, we looked for missing BUSCOs in a 184 9 species with a similar karyotype and higher score (D. athabasca) and found that 49% of missing 185 BUSCOs (20 of 41 total) were in pericentromeric regions.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…BUSCO results suggest our final scaffolded genome assembly is of high quality and 181 95.7% of BUSCOs were found complete (Table 1). We found the BUSCO statistics to be slightly 182 lower than our other high-quality obscura group assemblies which average 98.7% complete 183 (Bracewell et al 2019). To investigate this reduction, we looked for missing BUSCOs in a 184 9 species with a similar karyotype and higher score (D. athabasca) and found that 49% of missing 185 BUSCOs (20 of 41 total) were in pericentromeric regions.…”
mentioning
confidence: 86%
“…Therefore, residual genome assembly 186 and polishing issues of highly repetitive pericentromeric regions are likely the main contributor 187 to the slightly lower scores of D. bifasciata. Figure S3) and was also the most frequently encountered TE in 199 D. athabasca, which also has large metacentric chromosomes (Bracewell et al 2019).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…On an evolutionary timescale, tandem repeats change rapidly and are among the first sequence classes to diversify in emerging species (Charlesworth et al, 1994, Oliver et al, 2013, Zhang et al, 2015, McCann et al, 2018, Bracewell et al, 2019. Accumulation of mutations (single nucleotide changes, indels) leads to the emergence of new satDNAs variants, which may spread and displace existing variants and often form homogenised arrays (Plohl et al, 2012, Garrido-Ramos, 2015.…”
Section: Introductionmentioning
confidence: 99%